Development, implementation and dissemination: Couples and Parent–Child Communication Workshops in Zambia. Issue 4 (2nd April 2020) - Butts, Stefani A.; Langlie, Jake; Rodriguez, Violeta J.; Weiss, Stephen M.; Menon, Anitha; Hapunda, Given; Jere-Folotiya, Jaqueline; Mwaba, Sydney; Jones, Deborah L.
ABSTRACT: Over a million people are living with HIV in Zambia, representing ∼13% of the country's population. To increase HIV prevention communication, a community-based communication training program, the Parent–Child and Couples Communication Workshop, was developed from pilot data and culturally tailored for dissemination in Zambia. Workshop trainees ( N = 195) were 18 years of age or more and community educators and counselors in the Copperbelt and Southern Provinces of Zambia, e.g., peer educators, lay counselors, teachers, nurses, mentors and program officers, workshops ( N = 16) were conducted. Satisfaction with the workshops, readiness to conduct a workshop and implementation were assessed. Overall, readiness to conduct workshops following training and satisfaction with the workshop was similarly high across Provinces. Following the initial training, more than half of workshop trainees conducted workshops in their own communities. Zambian community members were receptive to learning techniques to disseminate communication strategies that could prevent HIV transmission. The use of culturally appropriate strategies and a training of trainers approach for communication and prevention may have enhanced workshop dissemination in Zambian communities. Future research should explore the use of culturally congruent HIV prevention initiatives in the Zambian context.